Salt of the earth :
Here was a film that presented housework, child care, sanitation as important political issues; that used humour to deflate macho attitudes; that recognised the necessity of rejecting the 'old way' but acknowledged the difficulty of creating something new; that had chosen a woman as protagonist and entrusted to her the role of narrator. Here was that rarity, a female hero who not only struggles and suffers but grows and wins. And she gains not simply in self-knowledge, not simply through wresting a piece of hard-won turf from an unchanged society; rather, her victory represents the shared triumph of the community - the specific victory of a successful strike, the less tangible victory of greater equality between Anglos and Mexican-Americans, women and men...